2007
DOI: 10.1016/j.jacc.2007.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Inhibition of the Mitochondrial Aldehyde Dehydrogenase Promotes Nitroglycerin Tolerance in Human Blood Vessels

Abstract: Long-term GTN treatment induces tolerance and endothelial dysfunction in human vessels, associated with an inhibition and down-regulation of vascular ALDH-2. Thus, these findings extend results of previous animal studies to humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 19 publications
6
51
0
Order By: Relevance
“…Among the various mechanisms that have been proposed to explain this nitrate tolerance (Fung, 2004;Mayer and Beretta, 2008), inactivation of ALDH2 (Chen et al, 2002) and superoxidemediated oxidation of GTN-derived NO (Mü nzel et al, 2005) are the most promising candidates at present. Denitration of GTN results in mechanism-based inactivation of ALDH2 (Beretta et al, 2008b), GTN-tolerant blood vessels exhibit markedly reduced ALDH2 activity (Sage et al, 2000;DiFabio et al, 2003;Sydow et al, 2004;Hink et al, 2007;Wenzl et al, 2009b), and ALDH2(Ϫ/Ϫ) mice do not become tolerant (Chen et al, 2005). Taken together, these results suggest that vascular tolerance to GTN is explained by inactivation of ALDH2.…”
Section: Introductionmentioning
confidence: 81%
“…Among the various mechanisms that have been proposed to explain this nitrate tolerance (Fung, 2004;Mayer and Beretta, 2008), inactivation of ALDH2 (Chen et al, 2002) and superoxidemediated oxidation of GTN-derived NO (Mü nzel et al, 2005) are the most promising candidates at present. Denitration of GTN results in mechanism-based inactivation of ALDH2 (Beretta et al, 2008b), GTN-tolerant blood vessels exhibit markedly reduced ALDH2 activity (Sage et al, 2000;DiFabio et al, 2003;Sydow et al, 2004;Hink et al, 2007;Wenzl et al, 2009b), and ALDH2(Ϫ/Ϫ) mice do not become tolerant (Chen et al, 2005). Taken together, these results suggest that vascular tolerance to GTN is explained by inactivation of ALDH2.…”
Section: Introductionmentioning
confidence: 81%
“…Whatever the nature of this chemical species, these findings found rapid human translation. For instance, incubation of human vessels with an ALDH-2 inhibitor recapitulated the abnormalities associated with the development of tolerance, 32 ( Figure 5) and a loss-of-function mutation of ALDH-2 particularly frequent in Eastern Asia and Eastern Europe was found to be associated with impaired GTN metabolism and reduced responsiveness to GTN. 33 …”
Section: Aldehyde Dehydrogenase the Enzyme That Metabolizes Alcoholmentioning
confidence: 93%
“…Subsequently, we demonstrated that GTN treatment stimulates the vascular (and particularly endothelial) production of peroxynitrite, a highly reactive intermediate generated from the rapid, diffusion-limited reaction of NO with O 2 ·Ϫ . 32,46 Evidence of GTN-induced increased ROS production in humans was then obtained ex vivo in arterial segments and in blood or platelets taken from patients rendered tolerant to GTN. 19,39,48,49 GTN tolerance was also associated with increased markers of free radical-induced lipid peroxidation such as cytotoxic aldehydes and isoprostanes 50 and esterified 8-epi-PGF 2␣ 51 and with a mild reduction in the responsiveness to the NO donor sodium nitroprusside in healthy volunteers, 4 which might also be compatible with ROSmediated interference with NO signaling.…”
Section: Does Oxidative Stress Account For Nitratementioning
confidence: 99%
“…That is, it is speculated that the activity and/or expression of aldehyde dehydrogenase (ALDH-2), a major enzyme responsible for nitroglycerin bioactivation, was decreased by pretreatment with nitroglycerin. In this regard, the decreased activity and expression of this enzyme in human vessels have been demonstrated to be induced by in vivo treatment with nitroglycerin (Hink et al 2007). Consequently, it is thought that the nitrate tolerance observed in the present study overlaps with, at least partially, that in the body.…”
Section: Discussionmentioning
confidence: 99%